Camchaya bolavenensis (Asteraceae: Vernonieae), a new species from Bolaven Plateau, southern Laos - Noyori, Wataru; Komada, Natsuki; Souladeth, Phetlasy; Tagane, Shuichiro (Phytotaxa, 2022)
A new species Camchaya bolavenensis (Asteraceae: Vernonieae: Centrapalinae) from Dong Hua Sao National Protected Area located in Bolaven Plateau, southern Laos, is described and illustrated. It resembles C. gracilis and C. thailandica in morphology but distinguished by its basally decumbent stem, margin of lamina with distinct (1–)2–3 teeth, 2–4 mm long on each side, invisible secondary veins, and a capitulum with 10–30 of florets.